Stan zdrowia osób w podeszłym wieku w kontekście starzejącego się społeczeństwa - Sacharczuk, Katarzyna (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2021)
The aging society is a challenge that must be faced on many levels. One of the most important tasks is to provide the growing group of elderly people with the best possible living conditions, also in terms of health. Health is an important value for Poles, which directly affects their quality of life and their opportunities for engaging in various activities. The following article discusses selected studies on the health condition of Poles over 60 and the subjects’ self assessment concerning health. These data are analysed against comparable research results for the inhabitants of the selected other European countries. To attain the research objective, the author analyses the data from the reports published by the Central Statistical Office, Eurostat, the Organization for Economic Cooperation and Development, and the results of the National Test for Poles’ Health. Focus is placed on issues such as: compliance with preventive recommendations, long-term health issues and chronic diseases, long-term limited capability to perform activities, use of medical consultations, hospitalisation, rehabilitation and surgical treatment, as well as subjective self-assessment of one’s health condition.